Improving The Quality of Education in A Collection of Poems Pada Suatu Musim by Bayu Suta Wardianto in Quality Education - Irma Widiastuti , Ade; Ma'ruf , Amin; Muktiyusrina, Evalasefa; Wulan Nurlaili, Fadilah; Awaliyah Nur Kamila Hakim, Hilda; Dhiya Ulhaq, Wafly; Nuraeni, Weni (International Proceedings of Nusantara Raya, 2023)
Education is an effort to improve the quality of life and human resources. Because education is the spearhead of a country to educate the nation's children. One of the goals of education is to increase student creativity in learning at school. Education based on local culture with various wisdom will be better for shaping character and developing self-potential than education sourced from cultures outside students. Education is the learning of knowledge, skills, and habits of a group of people passed from one generation to the next through teaching, training, or research. The etymology of the word education comes from the Latin ducare, meaning "to lead, direct, or lead" and the prefix e, meaning "out". So, education means the activity of " leading outwards". Poetry is an example of a literary work as a form of self-expression of a person expressed in the form of beautiful writing. In the poem entitled "Improving the Quality of Education" many teachings are tucked into every word, for example about life values such as educational, social, religious, and others. From here the researcher was moved to try to raise these life values into this study, so that lessons could then be taken. The purpose of this study is to explain the values of Education contained in the poem "Education" subjectively. This research uses qualitative descriptive methods with data collection techniques, namely literature study technique. The results of the research are known that there are many things from understanding and interpreting the improvement of the quality of education in a collection of poems in a season by Bayu Suta Wardianto in improving the quality of education. This can be seen in terms of educational, social, humanitarian, and religious aspects.